2020
DOI: 10.1617/s11527-020-1458-2
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy techniques for determining water–cement (w/c) ratio in hardened concrete: a round-robin assessment

Abstract: Water to cement (w/c) ratio is usually the most important parameter specified in concrete design and is sometimes the subject of dispute when a shortfall in concrete strength or durability is an issue. However, determination of w/c ratio in hardened concrete by testing is very difficult once the concrete has set. This paper presents the results from an interlaboratory round-robin study organised by the Applied Petrography Group to evaluate and compare microscopy methods for measuring w/c ratio in hardened conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Examples include the physicochemical method of BS 1881-124 (British Standards Institution, 2015 and petrographic methods such as fluorescence microscopy (Mayfield, 1990, Elsen et al, 1995, Sibbick et al, 2019 and backscattered electron microscopy (BSE) (Wong and Buenfeld, 2009, Wong et al, 2013, Yio et al, 2014. A recent round-robin assessment involving eleven laboratories in Europe (Wong et al, 2020) has demonstrated the viability of petrographic microscopy methods for determining w/c ratio in hardened concrete. The aggregate content and particle size grading can be determined by breaking down the cementitious matrix through mechanical, thermal or chemical (acid dissolution) treatments, followed by a sieve analysis of the remaining material (British Standards Institution, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the physicochemical method of BS 1881-124 (British Standards Institution, 2015 and petrographic methods such as fluorescence microscopy (Mayfield, 1990, Elsen et al, 1995, Sibbick et al, 2019 and backscattered electron microscopy (BSE) (Wong and Buenfeld, 2009, Wong et al, 2013, Yio et al, 2014. A recent round-robin assessment involving eleven laboratories in Europe (Wong et al, 2020) has demonstrated the viability of petrographic microscopy methods for determining w/c ratio in hardened concrete. The aggregate content and particle size grading can be determined by breaking down the cementitious matrix through mechanical, thermal or chemical (acid dissolution) treatments, followed by a sieve analysis of the remaining material (British Standards Institution, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to contrast enhancement for crack detection, FM shows the potential to illustrate the capillary porosity in the cement paste matrix of concrete [22,23]. One important application is to determine water to cement ratio (w/c) [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to contrast enhancement for crack detection, FM shows the potential to illustrate the capillary porosity in the cement paste matrix of concrete [22,23]. One important application is to determine water to cement ratio (w/c) [23]. More generally, the sensitivity of fluorescent light intensity on capillary porosity makes it an indicator of the microstructural alteration along the depth in cementitious materials subject to chemical attacks such as microbially induced corrosion [24].…”
mentioning
confidence: 99%
“…In addition to contrast enhancement for crack detection, FM shows the potential to illustrate the capillary porosity in the cement paste matrix of concrete [23,24]. One important application is to determine water to cement ratio (w/c) [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to contrast enhancement for crack detection, FM shows the potential to illustrate the capillary porosity in the cement paste matrix of concrete [23,24]. One important application is to determine water to cement ratio (w/c) [24]. More generally, the sensitivity of fluorescent light intensity to capillary porosity makes it an indicator of the microstructural alteration along the depth of cementitious materials subject to chemical attacks such as microbially induced corrosion [25].…”
Section: Introductionmentioning
confidence: 99%